Влияние нестандартных условий на термодинамическую вероятность совмещенного хемосорбционно-экстракционного процесса - Суворин, А. В.; Захаров, И. И.; Доценко, А. Д. (НТУ "ХПИ", 2006)
The results of calculations of influencing of non-standard terms on thermodynamics probability of chemical transformations in the system NiO-NOx-H2O-HNO3-Ni(NO3)2 are represented. It is shown, that the varying in the enough wide interval of the T, P, concentrations of the liquid and gas phases components, terms for accumulation of nitric acid in the system are absent and favorable terms for catching of nitrogen oxides and extraction of metals in solution from the spent catalysts are created.
Keywords: хемосорбция; оценка вероятности; термодинамическая вероятность